Effects of biomaterials keratin-gelatin and basic fibroblast growth factor-gelatin composite film on wound healing in dogs - Arul Jothi, N.; Thilagar, Sundararajan; Abdul Rahman, Sheikh Omar; M. Y., Kamaruddin; Ganabadi, Shanthi; Goh, Yong Meng; Mohd Yusoff, Sabri (Veterinary Association Malaysia, 2006)

(untitled)
Eighteen clinically healthy dogs weighing 10-15 kg body weight were used in this study over a 20-day period. They were allocated randomly into 3 groups of 6 animals each. After the creation of 5 cm x 5cm open wound, Group I was control treated with Gentamycin ointment. Groups II and ill were treated with keratin-gelatin and basic fibroblast growth factor (bFGF)-gelatin composite film respectively. On application, the keratin-gelatin and bFGF-gelatin composite film were well accepted by the animals without any adverse reaction. On clinical examination, Group II showed bright beefy red color granulation tissue with angiogenesis when compared to Groups I and ill. On bacteriological examination, Staphylococcus aureus, Pseudomonas, Escherichia coli, Proteus and Klebsiella species were isolated from all the groups. Mean percentage of epithelialisation, wound contraction and total healing were significantly better in Group II (P<0.05). Keratin is a biocompatible protein which does not interfere with the body's normal immunologic response and therefore it can be used in extensive wounds and also in non healing chronic wounds which need a trigger to stimulate the normal healing process. In extensive wounds when there is lack of autologous tissue, biomaterials like keratin-gelatin may be beneficial and can be used.